Fundamentals Of Entrepreneurship (ENT300): Lunch Shawl / Nurul Izzati Ahmad Shabri - Ahmad Shabri, Nurul Izzati (2020)
Lunchbox Enterprise is a business that produce scarfs for ladies’ wear. The main reason why the Lunchbox Enterprise want to produce scarfs for ladies’ wear are because to appreciate all the woman out there especially Muslims with producing ironless, easy shawl that can be wear comfortly in any weather without feel hot. So, after considering all the factors, I come out with one solutions which is The Lunch Shawl.